Synthesis and Characterization of LaF3:Ce Scintillator Material - Sukirman, Engkir; Purwamargapratala, Yustinus; Sugeng, Bambang; Wahyudianingsih, Wahyudianingsih; Gunawan, Indra; Ahda, Syahfandi; Sudjatno, Agus; Dimyati, Arbi (BRIN Publishing (Penerbit BRIN), 2023)
Synthesis and Characterization of LaF3:Ce Scintillator Material.Synthesis and characterization of the LaF3:Ce scintillator have been carried out. Synthesis was carried out using the co-precipitation method. In this study, the raw materials used were NaF, LaCl3•7H2O, and Ce(NO3)3•6H2O with ethanol and distilled water as a solvent; while surfactants were used oleic acid. In this study, the compound LaF3:0.2Ce was synthesized. The sample was characterized by using an X-Ray Diffractometer (XRD), a Scanning Electron Microscope (SEM), and a Spectrofluorometer. The analyzed data showed that the 82.6 weight fraction of LaF3:0.2Ce phase has precipitated accompanied by the formation of NaCl and C2Ce phases of 5.1 and 12.3 weight fraction, respectively. The NaCl phase is a by-product of the chemical reaction: xLaCl3•7H2O + zCeCl3•7H2O + 3NaF → LaxCezF3 + 3NaCl + 7H2O which could be removed from the precipitate solution by an appropriate separation method, while the C2Ce one appeared as a result of heating the sample at 400ºC. The LaF3:Ce scintillator sample shows the phenomenon of a bluish glow with a lifetime, t = 6 × 10-10 seconds even in the presence of a foreign phase. The existence of NaCl and C2Ce as a local environment still makes LaF3:0.2Ce has normal lifetime characteristics.